Robinow syndrome and fusion of primary teeth - Priti Sushil Jain; Tejashri Shreyas Gupte; Abdulkadeer M Jetpurwala; Shely Pratik Dedhia (Wolters Kluwer Medknow Publications, 2017)
Managing patients with rare genetic disorders is a challenge that dentists face often. Robinow syndrome (RS) is one such rare genetic disorder with <200 cases reported worldwide. RS demonstrates multiple craniofacial abnormalities and orodental disorders, which need to be taken into consideration by a dental practitioner while rendering dental care.